Análise histomorfométrica e imunoistoquímica da regeneração óssea com enxerto de Bio-Oss® e Gingistat® em seio maxilar de coelho - Colombo, Luara Teixeira [UNESP] (2016)
Bio-Oss® is a deproteinized bovine bone, which is chemically and structurally comparable to mineralized human bone. A system of interconnected pores promotes bone growth without any adverse tissue reaction associated with being reported. Gingistat® is a collagen-based material equine. The purpose of this study was to evaluate the ossification process two bone substitutes, Bio-Oss® and Gingistat® in maxillary sinus floor lifting through histomorphometric and immunohistochemical analyzes. For it were used 16 (sixteen) Albino rabbits undergoing surgery for lifting the membrane of bilateral maxillary sinus nasal access. The maxillary sinus on the right side was filled by Bio-Oss ® and the left was filled by Gingistat®.After periods of 7, 14, 21 and 40 days the animals were euthanized and jaw has been removed for processing and histomorphometric and immunohistochemical analyzes. Statistical analysis were made conducted through the comparison between the control group and the treated group.The statistical test that was used depend on the distribution of the results in relation to the normal curve. The percentage of new bone formation only has statistical significance using between groups in the period of seven days where the Bio -Oss® group had superior results. At the end of the study, both groups had similar bone formation, however the Gingistat® was reabsorbed ais quickly, leading to a great loss in the high area